Guidance on how to make Moringa Leaf Herbal Tea (Moringa Oliefera) as an Endurance Booster in Negeri Itawaka, Central Maluku Regency - Manik, Sri Elviana; Sufriadi, Sufriadi; Afriandi, Fadli; Maryati, Sri (CARE: Journal Pengabdian Multi Disiplin, 2024)
Moringa leaves or in other languages known as Moringa Oliefera is one plant type with abundant properties and benefits. Not only the leaves, it turns out that the stem bark and seeds of moringa plants' roots have their own benefits. The nutritional content in moringa plants contains vitamin A 6.8 mg more than vitamin A contained in carrots, vitamin C 220 mg, calcium which is higher than milk, protein 6.7 grams, potassium 440 mg/100 grams, and also contains vitamin B6. Hence, it is suitable for consumption as an immune enhancer. Still, it is necessary to create a product that is certain to be consumed frequently by the community but based on moringa leaves, after seeing the habits of the Itawaka people who like to drink tea, a tea bag with moringa ingredients was created. The purpose of this service is that the community can make herbal tea from moringa leaves in order to increase endurance and to be consumed as a substitute for sweet tea to reduce excess sugar content. The method used in this service is a form of training or guidance, carried out in 2 stages, first providing education/theory, second practicing how to make. This activity found the results that the Itawaka community was able to utilize moringa plants and take the existing nutritional content as an immune enhancer by turning moringa leaves into herbal tea bags.